The Role of the Institutional Environment in Circular Business Model Adaptation : Circular SMEs perspective - Elonen , Joona (My University, 2026)
Climate change has become part of our daily lives. However, in recent years global climate action has received less attention, reflecting geopolitical uncertainty. Challenges brought by climate change require active solutions from various stakeholders in society, including businesses, as the depletion of natural resources caused by the linear economy model does not support the sustainable continuation of business operations. The circular economy is an alternative economic model, that aims to keep materials in circulation longer, reducing environmental impact. The circular economy also has its challenges, as the transition requires resources and expertise from companies, as well as a clear and supportive operating environment. The circular economy has significant growth potential internationally and it creates value for both companies and their customers. This study focuses on the internal and external factors influencing the adaptation of circular business models in the EU market. Previous literature on circular business models has mainly focused on the key business models and their challenges and drivers. The literature has identified that the market is driven by institutional factors, that influence the local operating environment. Dynamic capabilities help companies to identify and respond to these changes in the market, by adapting their operations accordingly. In Europe, circular economy regulation is governed at the EU level, but decisions are implemented locally. Furthermore, customers and culture are strongly linked to adaptation, as the adoption of the circular economy and local practices varies across markets. The theoretical framework examines circular economy concepts and business models. The adaptation of business models is examined through external and internal factors by analysing institutional factors and the company’s dynamic capabilities. The data for this qualitative study is collected through semi-structured interviews, from four companies utilizing circular economy business models. The empirical findings discovered that market adaptation is not influenced by the business model itself, but rather by companies’ ability to adapt their operations to the institutional environment. The themes addressed in the study are strongly interrelated, as adaptation is strongly influenced not only by a company’s capabilities but the local operating environment and its changing conditions. The results indicate that a company’s resources, culture, and employees are seen as key capabilities. Institutional factors are strongly interrelated, and adapting to them is seen as necessary. According to the findings, although the EU plays a central role in regulation, there may be differences in the country-specific operating environment. Based on the results, companies can identify areas for development within their own organizations and understand the key impacts of institutional factors.

Ilmastonmuutoksesta on tullut osa jokapäiväistä elämäämme, kuitenkin viime vuosien aikana globaalit ilmastotoimet ovat jääneet vähemmälle huomiolle, heijastuen geopoliitti-sesta epävarmuudesta. Ongelmat edellyttävät aktiivisia ratkaisuja yhteiskunnan eri sidosryhmiltä, mukaan lukien yrityksiltä, sillä luonnonvarojen väheneminen lineaarisen talousmallin vuoksi ei tue liiketoiminnan kestävää jatkuvuutta. Kiertotalous on vaihtoehtoinen talousmalli, jossa materiaalit pyritään pitämään kierrossa pidempään, vähentäen luonnolle kohdistuvaa kuormitusta. Kiertotalouteen kohdistuu myös haasteita, sillä siirtymä vaatii yrityksiltä resursseja ja osaamista, sekä selkeää ja myönteistä toimintaympäristöä. Kiertotaloudella on paljon kasvupotentiaalia kansainvälisesti ja se luo arvoa niin yrityksille, kuin asiakkaillekin. Tässä tutkimuksessa keskitytään tunnistamaan kiertotalouden liiketoimintamallien adaptaatioon vaikuttavia sisäisiä ja ulkoisia tekijöitä EU markkinassa. Aikaisempi kirjallisuus kiertotalouden liiketoimintamalleista on pitkälti keskittynyt keskeisiin liiketoimintamalleihin, sekä niiden haasteisiin ja ajureihin. Kirjallisuudessa on tunnis-tettu, että markkinaa ohjaavat institutionaaliset tekijät, jotka vaikuttavat paikalliseen toi-mintaympäristöön. Dynaamiset kyvykkyydet edesauttavat yrityksiä tunnistamaan ja tarttumaan markkinan muutoksiin, muokkaamalla omaa toimintaansa institutionaalisen ympäristön mukaiseksi. Euroopassa kiertotalouden säätelyä ohjataan EU-tasolta, mutta päätöksiä toteutetaan paikallisesti. Lisäksi asiakkaat, sekä kulttuuri ovat vahvasti liitännäisiä adaptaatioon, sillä kiertotalouden omaksuminen ja paikalliset toimintatavat vaikuttavat yritysten toimintaan. Viitekehyksessä tarkastellaan kiertotalouden käsitteitä ja liiketoimintamalleja. Liiketoimintamallien adaptaatiota tarkastellaan ulkoisten ja sisäisten tekijöiden kautta analysoimalla institutionaalisia tekijöitä ja yrityksen dynaamisia kyvykkyyksiä. Tämän laadullisen tutkimuksen aineisto kerättiin puolistrukturoiduilla haastatteluilla, haastattelemalla neljää kiertotalouden liiketoimintamallia hyödyntävää yritystä. Empiirisistä tuloksista havaittiin, ettei adaptaatioon vaikuta itse liiketoimintamalli, vaan enneminkin yritysten kyky mukauttaa toimintaansa institutionaalisen ympäristön mukaiseksi. Tutkimuksessa käsitellyt teemat ovat vahvasti liitännäisiä toisiinsa, sillä adaptaatioon vaikuttaa vahvasti yrityksen osaaminen, mutta myös paikallinen toimintaympäristö ja sen muutokset. Tulokset osoittavat, että yrityksen resurssit, kulttuuri ja työntekijät nähdään keskeisinä kyvykkyyksinä. Institutionaaliset tekijät ovat vahvasti liitännäisiä toisiinsa ja niihin sopeutuminen nähdään tarpeellisena. Löydösten mukaan, vaikka EU:lla on keskeinen asema sääntelyssä, maakohtaisessa toimintaympäristössä voi olla eroavaisuuksia. Tuloksiin pohjautuen, yritykset voivat tunnistaa kehityskohteita omassa organisaatiossaan, sekä ymmärtää instituutionaalisten tekijöiden keskeiset vaikutukset.
Keywords: circular economy; business models; adaptation (change); sustainable development; small and medium-sized enterprises; institutions (formal organisation); institutions (social mechanisms); dynamic capabilities; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business